PEMBERDAYAAN MASYARAKAT BERORIENTASI KEMANDIRIAN (STUDI PADA MASYARAKAT PESISIR KECAMATAN CAMPLONG KABUPATEN SAMPANG) - Pusposari, Luthfiya Fathi; Umamah, Umamah; Dwi, Chania (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
The aims of this study are (1) Describe the type of business and empowerment strategies are carried out on a group of craftsmen in the District of Camplong; (2) Describe efforts to achieve self-sufficiency in the economy in a group of craftsmen in the District of Camplong; and (3) Describe the obstacles faced in the community empowerment program to achieve economic independence in the group of craftsmen in the District of Camplong. This study used a  qualitative approach various case studies. The collection of data are observation, interviews, and documentation. Data were analyzed by classified and reduction data, withdrawal the conclution. Results of this research show, First: Strategies undertaken MDW in community development programs in the District of Camplong includes 7 steps. The type of business of the group of which are: 1) Pastries An-Nur village Dharma in Camplong; 2). Mukenah Gallery 99 in  Tambaan villages; 3). Crackers Taddan in Taddan village; 4). Pastry Taddan in Taddan village; 5). Haji cap Ala Arabia in Taddan village; 6). Batik Mandangin in village Mandangin Island; and 7). Shoes in sejati village; Second: The efforts made by MDW to achieve economic independence in the group of craftsmen in the District of Camplong are: 1). Assistance to craftsmen / auxiliaries; 2). Changing the mindset of the community of workers / laborers to be a creator of employment / self-employment; 3). Facilitate group of craftsmen with the help of venture capital in the form of raw materials in accordance with their respective efforts; 4). Providing training for members of groups of craftsmen organized by the government or universities; 5). Building a partnership with a modern market in Sampang; Third: Obstacles encountered in community development programs in the district Camplong are: 1). Mindset and attitude of traditional society; 2). Weak human resources and low work ethic;  3).  Limited funding / capital; 4). Uncertified IRT and the limited marketing / network Keywords: independence and community empowerment